A Processing Algorithm for Separation of Cardiac and Pulmonic Activities Reflected in Microwave Doppler Spectra - Hayrapetyan, Hayk G. (Mathematical Problems of Computer Science, 2021)
The problem of azimuthal scanning of the human body by CW Doppler radar is considered. A mathematical method and processing algorithm for separation of oscillation activities of various internal organs in the microwave Doppler spectra is proposed.